The culturalization of gender action in the Iraqi theatrical address the play " Revelations as an example" (Al-Academy, 2022)
The culturalization of gender action occupies a wide range in culture, thoughts and modern studies as well as in fine arts and the ways of expressing them.       Theater, as one of these arts, plays roles in establishing the fundamental concepts that aims at stating the uncontrollable deed of the social community. It remains one of the most effective and suitable means to confine the uncivilized practices to overcome a certain crisis after gender and cyborg in societies.        The research concentrates on studying the culturalization of gender action in the Iraqi theatrical address because of the effect it has on the modernizing thought in arts and theater literature. It consists of chapter one which deals with the " curriculum frame " -the problem of the research. The importance of the research is quite evident in dealing with a certain concept after the gender and whatever signs and concepts related to it . That points out the relation between the individual and the oral overwhelming diminution as well as the personifying connectivity in the address of the theater show .         As for the goal of the research , it aims at  knowing the culturalization of gender action in the theater address.